2019
DOI: 10.1111/2041-210x.13287
|View full text |Cite
|
Sign up to set email alerts
|

epower: An r package for power analysis of Before‐After‐Control‐Impact (BACI) designs

Abstract: Before‐After‐Control‐Impact (BACI) designs are widespread in environmental science, however their implicitly hierarchical nature complicates the evaluation of statistical power. Here, we describe epower, an r package for assessing statistical power of BACI designs. The package uses Bayesian statistical methods via the r‐package INLA to fit the appropriate hierarchical model to user supplied pilot survey data. A posterior sample is then used to build a Monte Carlo simulation to test statistical power specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
0
27
0
2
Order By: Relevance
“…However, limited evidence indicated that those changes may have been happening in unflooded areas before dam closure. Stronger conclusions about these changes in species composition would be possible using a BACI design [ 74 ]. We recommend that environmental authorities require long-term monitoring and BACI designs in future environmental-impact studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited evidence indicated that those changes may have been happening in unflooded areas before dam closure. Stronger conclusions about these changes in species composition would be possible using a BACI design [ 74 ]. We recommend that environmental authorities require long-term monitoring and BACI designs in future environmental-impact studies.…”
Section: Discussionmentioning
confidence: 99%
“…We used a combination of MBACI and dose-response experimental designs (31) to monitor fishes within high-exposure (impact) and control sampling zones and at multiple sites that experienced varying levels of exposure to the seismic source within Area 3 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The MBACI sampling design provided a binary comparison between exposed and control zones (vessel control and control samples were pooled for analysis). The potential impact of exposure was measured as the difference in the response variable (e.g., abundance and length) before and after the seismic source exposure at a high-exposure (impact) zone, compared with the difference in the variable before and after the exposure at the vessel control and control zones (31). To demonstrate an impact, there must be statistical evidence for a significant difference in the measured variable between the high-exposure and control zones, after accounting for natural variability through time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most ecological time-series impact evaluation studies have focused on only one or a handful of time series [32][33][34][35][36][37], using only average change has not been a big problem, as each time series could be visually checked for indications of trends. However, risks increase when using large numbers of time series (e.g., counts of multiple bird species at multiple sites [38]), where checking individual series becomes impractical.…”
Section: Impact Evaluation With Time Seriesmentioning
confidence: 99%